Faktor-Faktor yang Mempengaruhi Meningkatnya Kadar Gula Darah Pasien di Klinik Fanisa Kota Pariaman dengan Menggunakan Analisis Faktor - farah khamsatul hasanah; Helma Helma (UNIVERSITAS NEGERI PADANG, 2019)
Abstract—Diabetes mellitus type 2 is a type of diabetes mellitus that is commonly found. Diabetes mellitus type 2 is a threat to human health in indonesia and the world, one of them is Pariaman city, specially in Fanisa Clinic. People with diabetes mellitus in Fanisa Clinic have increased from to year. The purpose of this research is to find out the factors influence th increasing of diabetics sugar blood Fanisa Clinic in Pariaman city. In this research used primary data, where there were 70 questioners given to the diabetics mellitus type 2 in Fanisa Clinic. The data having been obtained were analyzed by using factor analysis. The result of this research from 6 variables as age (x1), body mass index (x2), food supply (x3), medication compliance (x4), physic activity (x5) and, stress (x6), 5 variable obtained an reduced be chance two factors. The first factor influence by age variable and physic activity, meanwhile second factor influence by body mass index ,food supply and medication compliance. Keywords—Diabetes Mellitus, Blood Sugar Level , Factor Analisys.